Impact of Density Degree and Grade of Inorganic Binder on Behavior of Molding Sand at High Temperature - Stachowicz, Mateusz; Paduchowicz, Patrycja; Granat, Kazimierz (Journal of Casting & Materials Engineering, 2017)
This paper discusses the impact of high temperatures (up to 900°C) on molding and core sand with inorganic binders selected from among the group of unmodified grades of hydrated sodium silicate (water-glass). Molding sands with medium quartz sand were made under laboratory conditions and compacted at the different energy inputs necessary for obtaining various apparent densities (ϱ0). Due to the different composition and apparent density of molding mixtures hardened via microwaves at a frequency of 2.45 GHz, it was possible to assess their deformation (L) at a high temperature above the binder’s eutectic temperature. For this purpose, an apparatus for hot distortion tests was used whose construction and equipment allows us to measure the thermoplastic deformations in molding sand in many aspects; i.e., in its time of annealing. The article proposes new possibilities of interpreting the hot distortion phenomena in comparative studies of molding materials and mixtures. The application of this new measurement method revealed the differences between molding mixtures made with five inorganic binders with a molar module ranging from 2.0 to 3.4 and apparent density ranging from 1.34 to 1.57 g/cm3. It was established that distortions under the influence of high temperatures last the longest in molding sand with a binder with the highest molar module (3.4). Research also revealed that the density of molding sand is significant for increasing/decreasing the rate of thermoplastic deformations following the heating of samples only if the molding sand includes binders with a molar module of between 3.0 to 3.4. For molding sand with binders with molar modules from 2.0 to 2.5, it was established that this is excessively susceptible to thermoplastic deformation.